Disinfection of Dental Unit Water Line Using Aloe Vera: In Vitro Study - Sonia Pareek; Anup Nagaraj; Prateek Sharma; Mansi Atri; Satinder Walia; Shravani Naidu; Asif Yousuf (International Journal of Dentistry)
Context. Dental unit waterlines may be heavily contaminated with microorganisms and are a potential source of infection for both practicing staff and immunocompromised patients particularly. Contamination of dental unit water lines could be inhibited with the use of disinfectants. The present study investigates the effect of aloe-vera-based disinfectant in reducing the microbial growth in dental unit water lines (DUWLs). Aims. To compare the efficacy of aloe vera, hydrogen peroxide (H2O2), and 5% sodium hypochlorite (NaOCl) in controlling microbial contamination of DUWLs. Materials and Methods. After obtaining baseline water samples, the dental unit waterlines were treated with aloe vera, 10% hydrogen peroxide, and 5% sodium hypochlorite. Each of the three disinfectants was used in increasing concentrations and their inhibiting effect was compared. Water samples were analyzed for microbiological quality by the total viable count (TVC) method. Statistical Analysis Used. SPSS 16. Results. There was significant reduction in mean CFU/ml when treated with disinfectants each for a period of one week. Aloe-vera solution was found to be the most effective in reducing the microbial colonies. Conclusions. Improving the water quality from dental unit water lines is of considerable importance; chemical-based disinfectants can be replaced with herbal disinfectants for treating microbial contamination in dental unit waterlines.